(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Human papillomavirus (HPV) infection is associated with oropharyngeal and anogenital cancers in men and women. Approximately 90% of all cervical cancers are attributed to high-risk HPV infections, and 60% of squamous cell carcinomas (SCC) of the vulva, vagina, anus, and penis are due to HPV infection. Case presentation: We present the case of a 26-year-old with retroviral disease managed for locally advanced vulva cancer on external beam radiotherapy followed by wide excision of the residual tumor and bilateral inguino femoral nodal dissection. She later presented with a history of foul-smelling vaginal discharge. A biopsy confirmed moderately differentiated squamous cell carcinoma of the cervix clinically and radiologically staged at 2B and 3B, respectively. She was scheduled to start chemotherapy with carboplatin and paclitaxel after blood transfusion due to anemia. Discussion: Field cancerization was coined by Slaughter et al. to describe the existence of generalized carcinogen-induced early genetic changes in the epithelium from which multiple independent lesions occur, leading to the development of multifocal tumors. In some cases, multiple contiguous tumor foci coalesce, hence the lateral spread of squamous cell cancers. It was also observed that normal-looking cells near malignant cells were histologically abnormal and therefore were part of the transformed cells in a particular tumor field and consequently were responsible for the occurrence of local tumor recurrences. Conclusion: Field cancerization is a well-known and well-documented process of malignant transformation. Several studies have confirmed the importance of this phenomenon in tumor development. Surveillance is the key to detecting early recurrence and secondary malignancies.